Pendekatan Esensialisme Dalam Implementasi Problem-Based Learning Pada Pembelajaran Pendidikan Agama Islam - Annisaul Fitri; Maysi Adriani; Herlini Puspika Sari (STIKes Ibnu Sina Ajibarang, 2024)
His study discusses the application of the essentialism approach in the implementation of Problem-Based Learning (PBL) in Islamic Religious Education learning. Essentialism, as a conservative educational school, emphasizes the importance of maintaining cultural values ​​that have been tested by time. The purpose of this study is to identify how essentialism can support the problem-based learning process, so that students can discover and internalize the truth rooted in cultural heritage. The methods used include literature analysis on educational philosophy and classroom learning practices. The findings show that the essentialism approach encourages the use of lecture, dialogue, and discussion methods, as well as exploring relevant issues in the student's environment. The implications of this study emphasize the importance of the role of teachers as authorities in the classroom, as well as the need for discipline in the learning process, which is expected to strengthen students' character and understanding of religious values. Thus, the essentialism approach in PBL can make a significant contribution to more effective and meaningful Islamic Religious Education learning.